2001
DOI: 10.1095/biolreprod65.6.1718
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and Progesterone Metabolites and Follicle-Stimulating Hormone in the Aged Macaque Female1

Abstract: The study presented characterizes the ovarian and pituitary function of the aged female macaque through a complete annual reproductive cycle to compare hormone dynamics during the human and nonhuman primate menopausal transition. Data collected over an entire year from aged macaque females indicated that urinary FSHbeta subunit baseline levels statistically significantly increased in females after age-related abnormal menstrual cycles occurred. These abnormal cycles were followed by anovulation and complete ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 28 publications
4
64
0
3
Order By: Relevance
“…Despite the absence of seasonality in terms of food availability, individuals were still exposed to seasonal changes in day length and temperature, both important factors driving seasonal breeding and reproductive hormone secretion (Wingfield 1984). A negative correlation between fertility and age has been observed for a number of primate species including hanuman langurs (Presbytis entellus, Borries et al 1991), rhesus macaques (Macaca mulatta, Gilardi et al 1997;Shideler et al 2001) and olive baboons (Papio anubis, Strum and Western 1982). Although the average age of our captive female group was 3.6 ± 1.3 years (range: 2-5), thus at the chronological age of peak reproductive potential, the biological age of the ovaries could be at an advanced stage, influencing ovarian endocrine activity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the absence of seasonality in terms of food availability, individuals were still exposed to seasonal changes in day length and temperature, both important factors driving seasonal breeding and reproductive hormone secretion (Wingfield 1984). A negative correlation between fertility and age has been observed for a number of primate species including hanuman langurs (Presbytis entellus, Borries et al 1991), rhesus macaques (Macaca mulatta, Gilardi et al 1997;Shideler et al 2001) and olive baboons (Papio anubis, Strum and Western 1982). Although the average age of our captive female group was 3.6 ± 1.3 years (range: 2-5), thus at the chronological age of peak reproductive potential, the biological age of the ovaries could be at an advanced stage, influencing ovarian endocrine activity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Shideler et al (2001) monitored rhesus monkeys for a complete year and found that menstrual cycling in older females frequently ceased during the nonbreeding season. They also reported that the monkeys in their study did not exhibit a rise in baseline FSHb during the transition to menopause, although that has been reported in perimenopausal women (Santoro et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, there are also differences, namely the function of the ZR in adults and the female-specific and ovary-mediated controls of ZR function. Yet even these differences may not be as great as they would appear, given that increases in DS have been observed late in the menopausal transition among women (Lasley et al 2002) and female rhesus (Shideler et al 2001), when ovarian function ceases. The very fact that marmoset studies reveal ovarian related changes in adult ZR function and the additional correlation of changes in 17,20-lyase activity with zonal CYTB5 expression substantially underscore the importance of CYTB5 as a major regulator of 17,20-lyase activity in vivo.…”
Section: Discussionmentioning
confidence: 96%